Carotenoids Assist in Cyanobacterial Photosystem II Assembly and Function - Zakar, Tomas; Laczko-Dobos, Hajnalka; Toth, Tunde N.; Gombos, Zoltan (Frontiers in Plant Science, 2016)
Carotenoids (carotenes and xanthophylls) are ubiquitous constituents of living organisms. They are protective agents against oxidative stresses and serve as modulators of membrane microviscosity. As antioxidants they can protect photosynthetic organisms from free radicals like reactive oxygen species that originate from water splitting, the first step of photosynthesis. We summarize the structural and functional roles of carotenoids in connection with cyanobacterial Photosystem II. Although carotenoids are hydrophobic molecules, their complexes with proteins also allow cytoplasmic localization. In cyanobacterial cells such complexes are called orange carotenoid proteins, and they protect Photosystem II and Photosystem I by preventing their overexcitation through phycobilisomes. Recently it has been observed that carotenoids are not only required for the proper functioning, but also for the structural stability of phycobilisomes.